Gastric xanthoma is correlated with early gastric cancer of previously Helicobacter pylori‐infected gastric mucosa. Issue 2 (14th December 2020) - Shibukawa, Narihiro; Ouchi, Shohei; Wakamatsu, Shuji; Wakahara, Yuhei; Kaneko, Akira
Abstract: Background and Aim: Successful Helicobacter pylori eradication has been shown to prevent the development of gastric cancer (GC), but clinical evidence for factors that correlate with GC of previously H. pylori ‐infected gastric mucosa (after eradication or natural disappearance) is limited. The purpose of our study was to identify these correlative factors. Methods: We retrospectively examined data from patients with previously H. pylori ‐infected gastric mucosa. Data from 168 patients who developed early GC and underwent endoscopic submucosal dissection (Group C) and 835 patients with no history of early GC (Group NC) were compared. We extracted data on gender; age; complications from malignant disease and diabetes mellitus; American Society of Anesthesiologists (ASA) physical status classification; and endoscopic characteristics of atrophy (open type), intestinal metaplasia, and gastric xanthoma (GX). Correlations were determined with multivariate logistic regression analysis and propensity score matching. Results: A significantly higher proportion of patients had GX in Group C than in Group NC. Age, male gender, ASA physical status classification of class III or higher, complications from malignant disease, atrophy (open type), and the presence of intestinal metaplasia and GX were identified as factors that correlated independently with GC (odds ratio = 3.65; 95% confidence interval = 2.37–5.61; P  < 0.0001). Propensity score matching demonstrated that the prevalence of GC was also significantly higher in patients who were positive for GX (37.2% vs 18.3%; P  < 0.0001). Conclusion: GX was shown to correlate with early GC of previously H. pylori ‐infected gastric mucosa. Abstract : We compared the characteristics of 168 patients with gastric cancer (GC) of previously H. pylori‐infected gastric mucosa (after eradication or natural disappearance) to those of 835 patients without GC in order to investigate factors that correlate with early GC. Gastric xanthoma was shown to correlate with early GC.